2020
DOI: 10.1177/1055665620980226
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Assessment of Cervical Vertebrae Anomalies in Patients With Cleft Lip and Palate

Abstract: Objective: To evaluate the occurrence of cervical vertebrae anomalies (CVA) in patients with unilateral (UCLP) and bilateral cleft lip and palate (BCLP) using cone beam computed tomography (CBCT) examinations. Design: Retrospective assessment of CBCT images. Descriptive statistics were calculated. Fisher exact test or χ2 test was performed to evaluate the differences among each CVA between sex and type of cleft. Setting: School of Dentistry. Participants: One hundred fifty-one patients with cleft lip and palat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…5 Also, the patient discussed here presented with oro-facial defects like cleft palate and missing bilateral upper lateral incisors. de Rezende Barbosa et al 6 evaluated the occurrence of cranio-vertebral anomalies in cleft patients and found atlanto-occipital assimilation in 1.32% of study sample indicating the association with cleft defects.…”
Section: Discussionmentioning
confidence: 99%
“…5 Also, the patient discussed here presented with oro-facial defects like cleft palate and missing bilateral upper lateral incisors. de Rezende Barbosa et al 6 evaluated the occurrence of cranio-vertebral anomalies in cleft patients and found atlanto-occipital assimilation in 1.32% of study sample indicating the association with cleft defects.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with cleft lip and palate are at a higher risk of developing cervical vertebra anomalies than the general population. Rate Recent studies on the possible development of cervical spine abnormalities (CVA) in patients with cleft lip and palate found a higher overall incidence of CVA in patients with cleft lip and palate [25][26][27] . Datana S et al found that the incidence of cervical spine abnormalities was 20.…”
Section: Relationship Between Cleft Lip and Palate And Cervical Verte...mentioning
confidence: 99%